دور السياسة النقدية في تحقيق الاستقرار النقدي في الاقتصاد العراقي للمدة (( 2003- 2009 )) (المجلة العراقية للعلوم الاقتصادية, 2018)
The topic of monetary policy and its role in achieving stability and economic growth, a large controversy over the past four decades, especially after multiple tools and creating a modern monetary instruments increased the transmission channels of monetary policy to economic activity. The monetary policy of effective economic policies in the face of the phenomenon of inflation as an integral part and important parts and components of general economic policy of any country. The exercise of this policy through its role in influencing the size of the form in which the money supply consistent with the prevailing economic conditions in order to absorb excess liquidity injection or stream of new monetary economy. After transformation of the economic system in Iraq since (2003) toward a market economy and reliance on the forces of supply and demand in the economy, hastened the Iraqi Central Bank through its tools of cash to secure this transformation and activation mechanisms of the market economy through a series of technical procedures and legislative, as well as relying on indirect monetary instruments and modernization of the direct monetary instruments in light of the new phase.